Auditor Ethics as Mediating Audit Quality in Small Public Accountants - Reschiwati Reschiwati; Farida Fattah; Amrizal Amrizal (International Journal of Artificial Intelligence Research, 2022)
Testing and analyzing whether auditor ethics are able to mediate the factors that affect audit quality is the aim of this study. These factors are the Competence, Independence, and Due Professional Care of an auditor. The sampling technique used is purposive sampling. There were 105 auditors from 9 KAPs who filled out the questionnaire completely so that it could be processed. Data were analyzed using smartPLS software version 3.0.This study proves that competence, independence, and due professional care affect auditor ethics and audit quality. Auditor ethics is proven to be able to mediate professional competence, independence and due professional care which affect audit quality. The higher the level of competence and independence as well as the prudence of an auditor with good ethics, the higher the quality of the audit. These results also prove that the factors affecting audit quality do not differ between small and large KAPs